Efforts to Develop MSMEs in the 5.0 Era and Digitalization in Women's Clothing Stores in Surabaya City, East Java - Kurrotul Aini Rachman; Faiha Niyaf; Mashudi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study aims to analyze the development efforts of MSMEs in the era of 5.0 and digitalization in women's clothing stores in Surabaya City, East Java. Women's clothing MSMEs are one of the sectors that have great potential for development, but are also faced with the challenges of intense competition and changes in consumer behavior. Era 5.0, with its focus on the integration of advanced technology and human-centric approach, as well as the acceleration of digitalization, offers significant opportunities for MSMEs to improve competitiveness. This study uses a qualitative approach with a case study method on several women's clothing stores in Surabaya. Data were collected through in-depth interviews with MSME owners, participatory observation, and analysis of related documents. The results show that women's clothing MSMEs in Surabaya have used various digital strategies, such as the use of e-commerch platforms, social media for marketing, and digital payments. Development in the 5.0 era requires MSMEs to not only utilize technology, but also understand and adapt to customer needs more holistically. The main challenges faced include limited capital, lack of digital literacy among some MSME actors, and the need for conducive ecosystem support from the government and related parties. This research recommends training programs that focus on the adoption of 5.0 era technology, facilitating access to capital for digital investment, and collaboration between MSMEs to create innovation. Thus, women's clothing MSMEs in Surabaya can be more optimal in utilizing digitalization and era 5.0 opportunities to achieve sustainable growth.